THE PAROLE AND PURPOSES OF SENTENCING - Balqis, Wizna Gania (Tadulako University, 2019)
The policy of determination of parole has strong relevance to the correctional idea as correctional idea is one model of purposes of sentencing that was initiated in order to achieve the goal of modern criminal punishment, which is to improve the convict (resocialization). Parole, in addition to a way of implementing imprisonment, as well as a form of coaching outside of prison inmates, who have the same purposes with the correctional idea philosophy.Â As a form of coaching outside of prison inmates, parole can be viewed as a subsystem of correctional system, and it will positively contribute to the achievement of correctional goals, which is to educate and guide inmates in order to return to live as responsible citizens as well as for themself, family and society.